Біоадаптивне управління в корекції психоемоційних розладів у жінок із безпліддям та перенесеним пренатальним стресом - Семененко, Ілона Валентинівна; Semenenko, I. V. (My University, 2021)
Treatment of non-motor disorders in patients with infertility and prenatal stress (PS) is an important component of comprehensive treatment of the disease. This study examined the clinical effectiveness of a non-drug method of bioadaptive management - training based on biological feedback (BFB) in the correction of psychoemotional disorders in patients with infertility and prenatal stress. Object and methods of research. The study involved 41 patients with infertility and PS aged 22 to 45 years. Group I consisted of 21 women who underwent infertility treatment using in vitro fertilization and biological feedback, group II - 20 women who underwent treatment using in vitro fertilization without biological feedback. All patients were assessed for psychoemotional status on the Beck Depression Scale (BDI-II), tests for Spielberger-Khanin reactive anxiety, assessment of personal anxiety on the 1st day of observation, at the end of the course of BFB - training in group I and after 10±2 days in the comparison group. Results. There was a significant overall improvement in the psycho-emotional state of patients who underwent a full course of BFB - training at the end of therapy (p<0,05). There was a statistically significant difference between the level of certain psychoemotional disorders (in particular, anxiety, reduced stress resistance) of the studied groups (p<0,05). However, in contrast to group I patients who underwent BOS training, no statistically significant improvement in the psychoemotional status of group II patients during the observation period was found. Conclusions. BFB training can be considered as an appropriate component in the comprehensive treatment of psychoemotional disorders in patients with infertility and prenatal stress.
Bioadaptive Management in Correction of Psychoemotional Disorders in Women with Infertility and Endured Prenatal Stress
Keywords: infertility; prenatal stress; psychoemotional disorders; in vitro fertilization; bioadaptive management